Adolescent Endometriosis: Review of Clinical Presentation and Long-Term Issues. Issue 1 (January 2014) - Audebert, Alain
Endometriosis may affect adolescent girls. The scientific literature on endometriosis in adolescents is limited, and many aspects are still uncertain despite a growing number of related reports. The prevalence of endometriosis in adolescents is unknown, but in selected groups of patients undergoing laparoscopy, it has been found to be higher than 50%. The physiopathology of adolescent endometriosis has not been specifically shown. However, the presence of a family history and associated genital malformations are more frequently identified in adolescents with endometriosis. The clinical presentation of the disease in adolescents has been assessed by numerous prospective and retrospective studies, and the risk factors for the development of endometriosis are well-known. The recommended diagnostic strategy is actually well-characterized, even if an early diagnosis is hardly ever made. The therapeutic management is also more consensual, but not definitive because of a lack of prospective studies evaluating either short- or long-term results and the impact on the natural history of the disease. Finally, the long-term sequelae are still a burden, and many questions are unanswered, despite new insights provided by a few recent reports evaluating the progression of the disease and its effects on subsequent fertility. Further studies are needed to better assess these issues.